Relationship Between Smartphone Use During Work From Home (WFH) and Computer Vision Syndrome (CVS) - Benggu, Aldi; Syamruth, Yendris K; Oematan, Grouse T.S (Faculty of Public Health, Nusa Cendana University, 2022)
Computer vision syndrome is a group of eye and vision disorders due to prolonged use of smartphones. People who use their smartphone for 4 hours or more in a day are at risk of developing CVS. The results of a survey conducted on 10 students, there are 8 out of 10 students who have experienced CVS, with the most common complaints being tired eyes and headaches caused by smartphone use with a usage time of 4 hours / day. The purpose of this study was to identify CVS complaints and analyze the relationship between smartphone use in terms of gender, distance, length of rest and duration with CVS disorders in 2018-2020 FKM, UNDANA students during Work From Home (WFH). This type of research is analytic observational with a cross-sectional approach, the sampling technique uses stratified random sampling with a sample of 284 people and data collection uses a questionnaire in google form format. The results showed that as many as 247 students experienced CVS disorders with the most complaining symptoms being eye fatigue and the results of the chi-square test for the sex variable p = 0.250 (p>0.05) meaning there was no relationship between gender and the incidence of CVS, distance the use of p = 0.005 (p < 0.05) and the contingency coefficient = 0.165, it means that there is a very low relationship between the distance of smartphone use and the incidence of CVS, rest time p = 0.226 (p> 0.05) it means there is no relationship between rest time and the incidence of CVS, and duration of use p = 0.000 (p <0.05) and the contingency coefficient = 0.233 means that there is a low relationship between duration of use and the incidence of CVS. The conclusion is that the most complained of symptoms are eye fatigue and tension, while the least complaint is the eyes seeing twins and there is a very low relationship between distance of use and CVS, there is a low relationship between duration of use and CVS, while gender and rest time are not associated with CVS